Evaluation of sewage impact on environmental quality and mesozooplankton community in a highly eutrophic estuary of Argentina - Dutto, María Sofía (2012)
Eutrophication caused by human sewage is a growing phenomenon along coasts. Mesozooplankton abundance, community structure, and environmental quality were compared at two sites in the inner Bahía Blanca Estuary (BBE), Argentina, one receiving regional sewage discharge (Canal Vieja), and the other a non-impacted area (Bahı´a del Medio). Comparisons of mean abundance and multivariate analyses were performed to detect spatial and temporal variations in both environmental and biotic variables. Significantly higher amounts of nitrogen and phosphorus and lower oxygen and pH were recorded at Canal Vieja. Larvae of the detritivorous crab Neohelice granulata were more abundant at Canal Vieja, whereas the common estuarine copepod species Acartia tonsa was more abundant at Bahı´a del Medio, where the mesozooplankton community was typical for the estuary. Although mesozooplankton is likely to be adapted to the high organic matter content in the BBE, the environmental conditions at Canal Vieja appear to favour Neohelice granulata, and this species should be considered as a potential indicator of the impact of sewage in future monitoring programmes. Particulate organic carbon and chlorophyll a were not influenced by organic loading in this naturally eutrophic estuary.